(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
The fact that there is a red thread linking the name of Montale to that of Gianfranco Contini in the Einaudi catalogue, and that the poet entered and - after many vicissitudes - remained in the Turin publisher’s catalogue thanks to Contini, is certainly not a statement harbinger of great news for those in the know, nor are there many mysteries surrounding the relationship between the author and his first critic, following the publication of Eusebio and Trabucco. Nonetheless, going through the archival papers of Contini’s and Montale’s lives within the walls of Via Biancamano will allow us to trace a partly new path, which will show how, despite the fact that Montale’s titles published under the Struzzo banner are not numerically even remotely comparable to those of Mondadori, Montale became in fact - and also thanks to Contini’s action - an Einaudi author.